Climate change mitigation potential of green roofs: exploring urban heat island indicators and a green roof’s capacity to sequester carbon in the Flint Hills ecoregion - Alam, M. M. Lekhon (Kansas State University, 2022)
Green roofs have evolved as an important part of “sustainable development” initiatives around the world. With increasing global warming, many tools are needed, including living roof ecosystems, to reduce urban heat island and climate change impacts. Rooftop green infrastructure can enhance sustainable urban development by reducing atmospheric CO₂ due to its ability to reduce the energy consumption of a building and sequester carbon in plants and substrates. Green roof research indicates that temperature regulation atop buildings is quantifiable and demonstrates a crucial role in reducing the energy demand of a building. Additional environmental benefits of green roofs include improved air quality by removing pollutants from the air and reducing ambient CO₂ concentrations. Given different climates, researchers are uncertain as to what substrate types, depths, and plant combinations sequester the greatest amounts of carbon in green roofs across different ecoregions. Additional research is needed to understand the benefits and limitations of green roofs in specific locations such as the U.S. Great Plains. A two-growing-season-long study evaluated the carbon sequestration and thermal loading performance of two experimental green roof beds with different depths ~20 cm and ~10 cm and two substrate types in Manhattan, Kansas. Three plant mixes consist of Sedum only (A), Sedum + native grass mix (B), and native grasses + forbs (C). This study also makes connections to building energy performance. Soil samples were collected at depths of ~8-inch or ~20 cm and ~4-inch or ~10 cm in 2019 and 2020. The soil was analyzed for microbial community composition by PLFA (phospholipid fatty acids), Total Organic Carbon and Nitrogen, and microbial respiration. Root biomass was also determined. Three-way and four-way analysis of variance (ANOVA) and Tukey’s HSD post-hoc analyses were conducted using R version 4.2.0 and SPSS Statistics 29. New methods have been proposed in this study to use data from in-situ measurements of temperatures on building envelopes to estimate the rate of change in heat storage within the soil layer (Q-value). The research was inspired by the summation technique as this calculation procedure allowed the researcher to analyze the accumulation of data on soil moisture content and differences in green roof surface and sub-surface temperatures over time. In-situ sensors were used to measure soil moisture content and surface and sub-surface temperatures so that thermal properties crucial to understanding heat transfer could be examined. Soil (substrate) types (Kansas BuildEx® [K] and rooflite® extensive mc [R]) and substrate depth were the independent variables for this study, where the primary focus was on determining the significance of soil moisture of a green roof system in building energy performance. All APD-EGR beds were provided supplemental irrigation on an as-need basis. This two-year (2019 and 2020) analysis found that beds with the R substrate (with its lower bulk density, higher pore space, and lower water-holding capacity than substrate K) likely sequester a greater amount of C per substrate volume. Analysis of temperature data showed that the 4-inch bed at the APD-EGR with R substrate seems to work more efficiently during the building cooling season (with summertime HVAC use) considering both day and night times than the 4-inch bed with K substrate. Interestingly, substrate types do not seem to play a significant role in influencing Q-values in the wintertime and the deeper substrate (8-inch bed) appeared to have more positive Q-values that could improve building performance. Considering depth, the study finds that the thermal performance of two different depths (4-inch and 8-inch) are not similar in two time periods (summertime vs. wintertime). Therefore, suggesting a depth (shallower or deeper) that will improve the energy performance of a building for both time periods in the Flint Hills Ecoregion needs more long-time research and proper instrumentations to determine the approximate R-value (thermal resistance). The soil moisture content is very likely an important factor related to green roof system-induced building energy performance. The study concludes that in both cases of carbon sequestration and thermal performance, a shallower bed with R substrate may work better as a climate change mitigation strategy in the context of the Flint Hills Ecoregion. However, more research is needed to confirm this. From both studies (thermal and C sequestration), the moisture-holding capacity of different substrate types at different depths appeared to be the key factor in determining green roofs' climate change mitigation potential. A more precise understanding of these dynamic processes and systems is essential to improve design, implementation, and management of green roof ecosystems in support of sustainable building design and climate change mitigation.
Keywords: Experimental green roof systems; Climate change mitigation; Carbon sequestration; Building energy performance; Sustainability